An Annotated Catalog of the Iranian Coreidae, Rhopalidae, and Stenocephalidae (Hemiptera: Heteroptera: Pentatomomorpha: Coreoidea) - Ghahari, Hassan; Moulet, Pierre; Linnavuori, Rauno E.; Ostovan, Hadi (Zootaxa, 2012)
A study of Iranian Coreoidea, Alydidae excluded, has brought new geographical data on these bugs. Ninety-five species in 34 genera of three families, including, Coreidae (53 species), Rhopalidae (33 species), and Stenocephalidae (9 species), are listed as the fauna of Iran. The following species of Coreidae are new for the Iranian fauna: Fracastorius cornutus Distant 1902, Homoeocerus albiguttulus Stål 1873, and Prismatocerus borealis (Distant 1918).